Examining the efficacy of treatment outcomes for patients with pulmonary tuberculosis in Western China: A retrospective study in a region of high incidence - Jian Zhou; Jinlan Li; Yong Hu; Shijun Li (BMC Public Health)
Abstract Background Guizhou, situated in western China, exhibits a high incidence of pulmonary tuberculosis (PTB) alongside comparatively challenging medical and economic conditions. Our objective was to investigate the determinants influencing successful PTB treatment and their scope, aiming to provide a scientific foundation for targeted interventions and enhancing treatment efficacy. Methods Data encompassing all PTB cases registered in Guizhou’s China Disease Prevention and Control Information System from 2017 to 2022 were analyzed. Using the successful treatment rate as the dependent variable, initial univariate analysis of independent variables was conducted, followed by multilevel binary logistic regression analysis to assess variables demonstrating statistically significant disparities. Results A total of 139,414 patients (average age: 44 years) were included, with 64.41% male and 35.59% female. Among them, 47.57% were etiologically positive and 16.35% had comorbidities. The overall successful treatment rate was 95.77%, with a cure rate of 42.54%. Nine factors were identified to influence treatment success, including a higher proportion of females (OR = 1.178), students versus farmers (OR = 1.960), and etiologically negative cases (OR = 1.831). Initial treatment showed better success rates than retreatment (OR = 3.046), and patients without comorbidities had higher success rates than those with comorbidities (OR = 1.303). Fixed-dose combination therapy (FDC) also yielded better outcomes (OR = 1.296). Ethnic differences were noted, with the Miao group having lower success rates (OR = 0.874) and the Buyi group higher success rates (OR = 1.270) compared to Han. Age was another factor, with success rates decreasing in the 41–60 (OR = 0.731) and 61 + age groups (OR = 0.604). Conclusions Western China faces ongoing challenges in enhancing its PTB treatment capacity and should prioritize the promotion of FDC therapy. Risk factors that influence treatment outcomes for PTB include male gender, advanced age, belonging to the Miao ethnic group, occupation as a farmer, etiological positivity, retreatment status, and comorbidities such as diabetes and HIV/AIDS. Further investigation is warranted to explore the disparities in successful treatment rates among different ethnicities.